HUKUM LELANG OBYEK HAK TANGGUNGAN TERHADAP HARTA BERSAMA SETELAH PERCERAIAN TANPA PERSETUJUAN ISTRI PUTUSAN No: 25 PK/Pdt/2019 - Pupimbiddi Nasution (Jurnal Abdi Ilmu, 2021)
Decision Number: 25 PK/Pdt/2019 which is a re-examination of Decision Number: 222 K/Pdt/2017 which determines Zainul Arifin as the winner of the mortgage auction where in the implementation of the credit agreement and binding the mortgage there is an unlawful act where the object of the mortgage is joint property which in its implementation there is no agreement from either side of the wife, but the judge's decision ratifies the object of dispute in the auction that is carried out. So that it raises the question of how the legal provisions provide guarantees for joint assets that are carried out after a divorce that does not share joint assets. How is the validity of the Auction of Mortgage Objects for Joint Assets where one of the parties is not regulated according to laws and regulations. What is the law on the judge's consideration in decision No: 25 PK/Pdt/2019 regarding the auction of mortgage objects carried out by the husband without the wife's consent. Which was finally entitled "Juridical Review of the Execution of Auction Objects Derived from Joint Assets (Study of Decisions) No: 25 PK/Pdt/2019). This type of research is normative legal research, namely research conducted by analyzing written laws from library materials or secondary data and reference materials in the field of law or references in the field of law. The data used to answer the problems in this research is secondary data that comes from library research. The legal provisions for the provision of guarantees for joint assets carried out after divorce that do not share joint assets cannot be carried out if there is no agreement between the divorced husband/wife. The execution of the Mortgage Rights gives authority to the first Mortgage holder to sell the object of the Mortgage on its own power through a public auction and take activities from the proceeds of the sale. The issue of joint property must be carried out in the Religious Courts because both spouses are Muslims and have the authority and authority of the Religious Courts to resolve marital problems in Indonesia. The auction of mortgage rights on joint assets that is carried out is legally valid even without the wife's consent because of the executive power of the mortgage. The good faith committed by the auction winner who needs to be protected in this case excludes the unlawful acts committed by the debtor who negligently did not seek approval from the plaintiff as his ex-wife. It is recommended for husband and wife to immediately carry out the distribution of joint assets so as not to injure the rights of others, then the implementation of mortgage auctions on joint assets must also be carried out carefully. returns where the good faith that was carried out must also apply to the auction seller, where the auction seller is responsible for the goods to be auctioned.